The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 7th International Scientific and Practical Conference "Current Issues of Linguistics and Didactics: The Inte 2017
DOI: 10.2991/cildiah-17.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of WEB resources use in learning process

Abstract: Abstract-The article deals with the issues of using Web resources in the learning process. They represent basic information about the possibility to create comfortable environments for learning processes by creating information and communication learning environments. The tasks that inspired genuine collaborative learning were characterized by a certain complexity in terms of multimodality and technology, or professional knowledge combining academic and practical experience. The authors stress the main advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…For instance, watching videos available on online platforms has shown that it could provide opportunities for second language learners to learn authentic English (Morat et al, 2017). Other than that, gaining resources from online web browser is invaluable in assisting self-directed learning among learners by providing information that suits their professional interests and needs for ESL learning (Erenchinova & Proudchenko, 2017). Finally, online interaction between one mobile user to another allows learners to practice using the English language in real world situations (Nishanthi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, watching videos available on online platforms has shown that it could provide opportunities for second language learners to learn authentic English (Morat et al, 2017). Other than that, gaining resources from online web browser is invaluable in assisting self-directed learning among learners by providing information that suits their professional interests and needs for ESL learning (Erenchinova & Proudchenko, 2017). Finally, online interaction between one mobile user to another allows learners to practice using the English language in real world situations (Nishanthi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Horun [17], N. Matochkina and A. Kinderknekht [18]. The advantages of using web resources in learning have been discussed by E. Erenchinova and E. Proudchenko [19]. The Russian experience of using Internet resources for educational purposes is presented by Ye.…”
Section: Introductionmentioning
confidence: 99%